The effect of Capitalism Expansions on Maximizing the Value of the Company: Profitability as a Mediating Variable” (Analytical Study for a Sample of Companies Registered in Iraq Stock Exchange for the Period from 2010-2021). - Badrawi, . Abid AL_ Reda; Ajaj , Mohammed (The Gulf Economist, 2023)
The study aimed to demonstrate the effect of (capitalism expansions) as an independent variable in (maximizing the value of companies) as a dependent variable through (profitability) as an intermediate variable. For the purpose of achieving the objectives of the study, an intentional sample of companies registered in the Iraqi Stock Exchange were selected. They are divided as from the industrial sector (7) companies and the hotel sector (5) companies, with a total of (12) companies, for a period from 2010 to 2021, with a number of 144 observations. The study relied on a set of financial methods using (Excel) program, statistical methods, linear regression analysis, and path analysis using SPSS and AMOSS programs. The study reached a set of conclusions, the most important of which is that the results of the statistical analysis showed that capital expansions are still statistically significant in terms of profitability, and that profitability is still statistically influential in the value of the company, i.e., profitability has full mediation and the effect is only through it. It reached a set of recommendations, the most important one is the need to raise the level of the company’s value by studying sample companies, which represents the main objective of the companies by focusing on capital expansion decisions and achieving rewarding levels of profitability, which reflects the value of the company.